SISTEM INFORMASI PERSEDIAAN BARANG BERBASIS WEBSITE (STUDI KASUS CV UNI PRATAMA). - Muhamad Iqbal Ardana (2022)
The use of information technology is currently growing so rapidly in all fields, and has a very large influence on various aspects of human life, both for individuals and organizations. Inventory is one of the main factors in the organization to support smooth sales. This research was conducted to create an inventory information system at CV Uni Pratama. CV Uni Pratama is a company engaged in the procurement of goods in the form of stationery. The purpose of this research is to build an information system to be able to assist in recording, managing and can facilitate monitoring of data items. To achieve the objectives of this study, the author uses the PIECES method to perform system analysis, and the waterfall method for system development to make it more systematic. To model the specifications or design of the system created, UML will be used. In designing the system the author will use the HTML, CSS, Java Script, and PHP programming languages. As for the database using MySQL. The result of this research is a webbased inventory information system which is expected to be useful and can solve problems regarding inventory at CV Uni Pratama. Keywords: Information System, Inventory, Waterfall, and Website.